Injection Moulding of Multipolar Polymer-Bonded Magnets into Soft Magnetic Inserts for Rotors in Reluctance Motors - Rösel, Uta; Drummer, Dietmar (Magnetism, 2021)
Due to lower magnetic properties of polymer-bonded magnets compared to sintered magnets, a complete redesign of the multipolar soft magnetic flux barriers in rotors with alignment guidelines was carried out to eliminate the frequently used rare-earth magnets, causing a new influence of the outer magnetic field on the cavity by using soft magnetic inserts. Within this new process, the main influencing factors on the magnetic flux density such as filler content, tool temperature, holding pressure and injection velocity were analysed and correlated. The studies were based on the compound of Polyamide 12 and up to a 60 vol.-% of the hard magnetic filler, strontium ferrite. Based on the study, the injection moulding of multipolar-bonded magnets into soft magnetic inserts for rotors and, in turn, into complex geometries can be optimized in terms of the orientation of the filler, the microstructure and the magnetic flux density. The investigations show no significant influence of the process parameters known from the literature such as the mass temperature Tm, which affects the magnetic flux density, as well as the orientation and the microstructure similar to tool temperature Tt, but is less efficient. The main influencing factors identified during the investigations are the tool temperature Tt, the injection velocity vin and the holding pressure ph. As known influencing factors are only based on simple geometries such as ring structures or plates, new factors were determined for complex rotor geometries.<br
Keywords: moulding compounds; magnetic flux density; optical microscopy; injection moulding; reluctance motor